High energy density carbon supercapacitor with ionic liquid-based gel polymer electrolyte: Role of redox-additive potassium iodide. (March 2022) - Hor, Abbas Ali; Yadav, Neetu; Hashmi, S.A.
Highlights: Non-aqueous redox gel polymer electrolyte is prepared with ionic liquid and KI. RGPE film with σ ∼3.9 × 10 −3  s cm −1 and ESW ∼5.05 v is suitable for supercapacitor. Redox-active carbon supercapacitor with RGPE offers capacitance of ∼240–260 f g − 1 . Specific energy increases from ∼35 to ∼70 wh Kg −1 with KI-incorporated electrolyte. Supercapacitor offers reasonable cycling performance up to 10, 000 GCD cycles. Abstract: Carbon supercapacitors with quasi-solid and flexible gel polymer electrolytes (GPEs) are of current interest due to their potential applicability as commercial power sources. In the recent development, improvement in specific energy of such devices is the main focus of research. Enhancement in interfacial redox-activity by adding appropriate redox-agent in electrolyte is found an excellent method to improve specific energy. In this report, a free-standing, non-aqueous, redox-active GPE is presented comprising an ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide added with additive KI, entrapped in poly(vinylidene fluoride-co-hexafluoropropylene) for its application in quasi-solid-state-supercapacitors. The optimum composition of GPE shows flexible nature, excellent mechanical and thermal stabilities with high ionic conductivity (3.9 × 10 −3 S cm -1 at room temperature) and wide electrochemical stability (∼5.05 V versus Ag). Carbon supercapacitor is fabricated with redox-active GPE and symmetrical electrodes of porous activated carbon (AC) derived from waste-biomass pollen-cone. The incorporation of KI in GPE instils fast redox-activity at the AC-electrode/GPE interfaces, hence, found responsible for substantial improvement in capacitance (from ∼115 to ∼250 F g − 1 ) and energy (from ∼31 to ∼65 Wh kg −1 ) at maximum power of 34–36 kW kg −1 . The supercapacitor with redox-active GPE demonstrates reasonable self-discharge behavior and cycling performance with only ∼11% initial fading. The capacitor offers retention rate of ∼70% in specific capacitance and energy after ∼10, 000 charge-discharge cycles. Graphical abstract: Image, graphical abstract